1996
DOI: 10.3109/00016349609054714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroxine therapy on bone metabolism in postmenopausal women with hypothyroidism

Abstract: Our study suggests that thyroxine replacement therapy in patients with suppressed thyroid stimulating hormone levels increases postmenopausal bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…A longer duration of levothyroxine therapy seemed not to be associated to reduced bone mineral density as most studies found no correlation of therapy length and bone mineral density (Florkowski et al, 1993;Franklyn et al, 1992;Frusciante et al, 1998;Fujiyama et al, 1995b;Giannini et al, 1994;Görres et al, 1996;Hanna et al, 1998;Hawkins et al, 1994;Kung and Pun, 1991;Kung et al, 1993;Langdahl et al, 1996;Marcocci et al, 1994;1997;Müller et al, 1995;Ongphiphadhanakul et al, 1996;Radetti et al, 1993;Stall et al, 1990;Tümer et al, 1999) and in few studies therapy length correlated negatively to bone mineral density (Affinito et al, 1996…”
Section: Patient and Treatment Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…A longer duration of levothyroxine therapy seemed not to be associated to reduced bone mineral density as most studies found no correlation of therapy length and bone mineral density (Florkowski et al, 1993;Franklyn et al, 1992;Frusciante et al, 1998;Fujiyama et al, 1995b;Giannini et al, 1994;Görres et al, 1996;Hanna et al, 1998;Hawkins et al, 1994;Kung and Pun, 1991;Kung et al, 1993;Langdahl et al, 1996;Marcocci et al, 1994;1997;Müller et al, 1995;Ongphiphadhanakul et al, 1996;Radetti et al, 1993;Stall et al, 1990;Tümer et al, 1999) and in few studies therapy length correlated negatively to bone mineral density (Affinito et al, 1996…”
Section: Patient and Treatment Characteristicsmentioning
confidence: 98%
“…High quality studies also found the same mixture of outcomes across both dose categories and all study designs, with differing effects being reported by an almost equal number of studies. No effects were found by 3 studies (Franklyn et al, 1992;Guo et al, 1997), mixed effects mostly by older studies (Adlin et al, 1991;Franklyn et al, 1994;Kung and Pun, 1991;Müller et al, 1995), and overall bone mineral loss by 3 studies (Affinito et al, 1996;Kung et al, 1993) among these the only large, new study using QUS (Hadji et al, 2000).…”
Section: Patient and Treatment Characteristicsmentioning
confidence: 99%
“…The detrimental effect of thyroid hormones appeared more marked on cortical bone than on trabecular bone [26]. We will briefly review the major studies appeared in literature afterwards which can be divided into those showing a detrimental effect of LT4 on BMD and those showing no such an effect [1224]. A summary of the main features of these studies is reported in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, foi demonstrado que a osteopenia em ratas hipertireóideas não é progressiva e que a responsividade do osso aos hormônios tireoidianos varia de acordo com o indivíduo, com o sítio ósseo e com o tempo de administração da tiroxina (47). A maioria dos autores considera a osteoclasia como o principal processo de reabsorção óssea (75,94,95), mas foi demonstrado que a reabsorção induzida pelo hipertireoidismo se dá muito mais pela atividade dos osteócitos profundos, ou seja, pela osteólise osteocíti-ca, sendo a osteoclasia pouco atuante (47). Embora os osteócitos apresentem receptores para o PTH, sua participação como mediador da reabsorção óssea induzida pelo hipertireoidismo é controversa e não foi ainda elucidada (87,90,96,97).…”
Section: Ribeiro Et Alunclassified